2017
DOI: 10.1590/1809-4430-eng.agric.v37n4p727-738/2017
|View full text |Cite
|
Sign up to set email alerts
|

Drying Kinetics of Niger Seeds

Abstract: ABSTRACT:The objectives of this study were to describe the process of drying niger seeds through the fitting of different mathematical models to the experimental drying data, to select the best model that represents the phenomenon, and to determine the diffusion coefficients and thermodynamic properties of the product. Seeds with an initial moisture content of 0. , and 80ºC in a fixed bed experimental dryer. After drying, different mathematical models were fitted to determine the diffusion coefficient by apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
4
1
Order By: Relevance
“…These values corroborate those found by Oliveira et al (2014) in their study with drying of soybean grains at temperatures between 40 and 100 ºC, as these authors observed effective diffusion coefficients between 0.84 and 3.46 x 10 -11 m 2 s -1 . However, the values are below those found by Silva et al (2017a), who observed effective diffusion coefficients from 2.32 to 15.69 x 10 -11 m 2 s -1 in the drying of niger seeds at temperatures between 40 and 80 °C. Bezerra et al (2015) found higher results for the effective diffusion coefficients (0.3199 to 1,994 x 10 -8 m 2 s -1 ) for the drying of passion fruit peel at the temperatures of 50, 60 and 70 °C.…”
Section: Acontrasting
confidence: 72%
“…These values corroborate those found by Oliveira et al (2014) in their study with drying of soybean grains at temperatures between 40 and 100 ºC, as these authors observed effective diffusion coefficients between 0.84 and 3.46 x 10 -11 m 2 s -1 . However, the values are below those found by Silva et al (2017a), who observed effective diffusion coefficients from 2.32 to 15.69 x 10 -11 m 2 s -1 in the drying of niger seeds at temperatures between 40 and 80 °C. Bezerra et al (2015) found higher results for the effective diffusion coefficients (0.3199 to 1,994 x 10 -8 m 2 s -1 ) for the drying of passion fruit peel at the temperatures of 50, 60 and 70 °C.…”
Section: Acontrasting
confidence: 72%
“…The effective diffusion coefficient of the mesocarp of baru fruits increased proportionally to the increase of the drying air temperature (Figure 2), showing a behavior similar to that of other products: niger seeds (Silva et al, 2017), sunflower seeds (Smaniotto et al, 2017) and 'pequi' pulp (Sousa et al, 2017).…”
Section: Resultsmentioning
confidence: 53%
“…The diffusion coefficient (D) serves as an indicator of the speed with which water is removed from a product (Silva et al, 2017b), which can be influenced by the increase in drying air temperature (Smaniotto et al, 2017), and results in reduction of water viscosity, facilitating its removal from the capillaries of leaves. An increase of D was observed as the drying air temperature increased during the drying of C. pachystachya leaves.…”
Section: Resultsmentioning
confidence: 99%